Coping strategies of manic depressives. [article]. - Encarnacion, Ruben L.
In a two-randomized groups design, twenty bipolar(manic depressive) subject answered questionnaires to explore what coping patterns(DV) are utilized by bipolars to maintain functionality. These twenty Ss were divided into high-functioning and low functioning groups (IV). Taken all together, the pre-identified coping strategies -Biochemistry/Lithium Compliance, Self-monitoring, Keen and Peer Support, Work, Creative/Athletic Pursuits, and Confidentiality-were found to be not significant in determining whether a bipolar subject would be high or low-functioning. However, two trends were found (p<.10): (a)High functioning bipolars tend to have more continuous work that they find fulfilling, and (b)Low-functioning bipolars tend to be more secretive about their condition. Since high-functioning bipolars tended to belong to high SES, SES as a possible confounding variable is discussed. Psychotherapy, group therapy, and the psycho-educational approach for the patients' families are presented as recommendations.